2006
DOI: 10.1097/01.bcr.0000202644.17987.3f
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic Malignant Syndrome Associated With Metoclopramide in a Burn Patient

Abstract: Neuroleptic malignant syndrome (NMS) is an uncommon, potentially fatal syndrome that occurs with the use of neuroleptic medications. In view of the rarity of this syndrome and the overlap with the pathophysiologic manifestations of a burn, the burn surgeon may not readily recognize NMS on presentation. We describe the case of a 27-year-old man with 15% TBSA burns who developed NMS as a result of metoclopramide use. Recognition and treatment resulted in a prompt resolution of symptoms. Initial treatment should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Use of metaclopromide alone has resulted in cases of NMS (Nachreiner et al 2006). Close attention must be paid when these agents are used with other dopamine agonists or antagonists.…”
Section: Neuroleptic Malignant Syndromementioning
confidence: 98%
“…Use of metaclopromide alone has resulted in cases of NMS (Nachreiner et al 2006). Close attention must be paid when these agents are used with other dopamine agonists or antagonists.…”
Section: Neuroleptic Malignant Syndromementioning
confidence: 98%
“…It was also described elevation of amylase and lipase in the setting of this syndrome [5]. Robb et al [8] have described elevation of creatinine phosphokinase levels [7] (CPK) and white blood cells (WBC), electrolyte abnormalities and myoglobinuria.…”
Section: Introductionmentioning
confidence: 96%
“…Prager et al [20] and Lavie et al [21] reported the difficulty of diagnosing NMS [5,20,21]. Symptoms and signs can vary depending on the patient condition and the drug used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations